PEMAKNAAN MEME STIKER WHATSAPP SEBAGAI BENTUK EKSPRESI MILENIAL - Aryo Bimo (Jurnal Ilmu Komunikasi Acta Diurna, 2021)
This digital era has made human interaction, which was done face-to-face, switch to using conversation applications or social media. A meme is a popular digital object that people can save, share and create / modify. One of these memes is a WhatsApp sticker. WhatsaApp is a conversation application that is often used in the digital age. Millennials who were born in the digital era have made WhatsApp a medium to interact with each other. Interactions that were in the form of symbols in the form of language, gestures, expressions were replaced with WhatsApp sticker memes. The phenomenon that occurs on WhatsApp is the use of stickers. These stickers can be classified in the meme category because they are digital objects in the form of photos or illustrations complete with text and can be shared with other people, and can be changed or modified by each user. This research is based on the author's assumption that millennials communicate through meme stickers as a form of self-expression within the framework of symbolic interactions. The purpose of this research is to prove this assumption. This research uses a qualitative method and is seen from the theory of symbolic interaction by interviewing several millennials to see how these millennials use WhatsApp stickers based on the symbolic meaning of the stickers related to themselves. Symbolic interaction is a process of interpreting actions because symbolic meanings can be formed differently for each person. The goal to be achieved is to see whether the use of WhatsApp stickers is interpreted as self-expression that appears as a result of actions to respond to what happens in interactions with other people. The results showed that the exchange of symbols that occurred with WhatsApp stickers was interpreted and used to respond to an interaction that occurred.